Flicker noise hy random walk of electrons at the interface in nonideal Schottky diodes - Lee, JI; Brini, J; Chovet, A; Dimitriadis, CA (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
An explanation of low frequency 1/f noise in nonideal Schottky barrier diodes is presented where the current fluctuation is attributed to the random walk of electrons at the metal-semiconductor interface via modulation of the barrier height. The experimental results on TiN/n-Si Schottky diodes have been successfully analysed to give useful information on the interface states. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: BARRIER DIODES; 1/F NOISE